(untitled) (Acta Scientiarum. Agronomy, 2023)
The center of origin and domestication of Piper nigrum L. are in high rainfall regions. But when grown in regions with irregular or insufficient rainfall, irrigation becomes essential. This study evaluated the impact of irrigation levels on the physiological and growth characteristics of black pepper plants, cv. Bragantina. It was carried out from April 2019 to May 2020, using automatic activation irrigation. We used emitters with different flow rates to apply water depths corresponding to 100, 81, 62, and 42% of the crop water requirement. The parameters evaluated comprised main stem length (MSL), stem diameter (SD), number of leaves (NL), leaf area (LA), chlorophyll contents, chlorophyll-a fluorescence, and some photosynthetic parameters. The treatments significantly influenced (p < 0.05, F-test) MSL and NL. Plants submitted to the control treatment showed MSL (65.8%) and NL (123%) greater than those irrigated with the smallest volume (p < 0.05, F-test). However, the treatments had no significant effect on SD. Moreover, chlorophyll b levels decreased by 26% and chlorophyll a/b ratio increased by 22% at 120 and 180 DAT, respectively. Some photosynthetic parameters such as FV/FM, ABS/RC, and DI0/RC were affected by water deficit at 120 DAT. Our results suggest the sensitivity of black peppers to water deficit and contribute to the proper management of this crop.